Study Analysis of Total Bilirubin Levels on Mortality in COVID-19 Patients: A Single Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Suhardi, Suryo Nugroho; Rikarni; Dwi Yulia (HM Publisher, 2024)
Background: Coronavirus Disease 2019 (COVID-19) is caused by a positive single-stranded RNA virus. The clinical manifestations of COVID-19 are not only dominated by respiratory tract symptoms but can also show symptoms of liver damage in severe COVID-19 patients. Liver damage that occurs can cause acute liver failure and result in death. Examination of liver damage marker parameters such as total bilirubin needs to be carried out as mortality increases in COVID-19 patients. This study aims to determine the relationship between total bilirubin levels and mortality in COVID-19 patients. Methods: Cross-sectional analytical research was conducted on 40 COVID-19 patients treated at Dr. M. Djamil General Hospital Padang from July to December 2021. Examination of total bilirubin levels using the colorimetric diazo method. Bivariate analysis used the Mann-Whitney test to see the relationship between total bilirubin levels and mortality. Results: The average age of the research subjects was 61.85 (1.40) years, with 65% men and 35% women. The mortality percentage in COVID-19 patients is 65%. The median total bilirubin level was 1.95 (0.5-2.8) mg/dL. The relationship between total bilirubin levels and mortality in COVID-19 patients was found to have a p-value of <0.001. The study results showed that the median total bilirubin level in COVID-19 patients who died was relatively higher, namely 2.20 (1.4-2.8) mg/dL, compared to those who did not die, namely 0.70 (0.5-1. 6) mg/dL. Conclusion: The results of this study show that there is a relationship between total bilirubin levels and mortality in COVID-19 patients.